2015
DOI: 10.3109/13697137.2015.1031214
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of endometrial fluid collection in asymptomatic postmenopausal women

Abstract: The results indicate that EFC in asymptomatic postmenopausal women is a benign condition, influenced by older age and commensurately longer menopause duration due to a lack of hormonal stimulation. The presence of EFC by itself does not affect the decision to provide further evaluation; that is determined by the presence of confirmed risk factors (e.g. thickened endometrial stripe). However, further studies are needed to assess any long-term prognostic impact of this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Tal achado, entretanto, constitui um viés do estudo, visto que tais pacientes possuíam também espessamento endometrial. Topçu et al (2015) analisaram o endométrio de 141 pacientes na pós menopausa com presença de líquido intracavitáro na USTV e não foi encontrada nenhuma patologia pré maligna ou maligna. Takacs et al (2005) analisando retrospectivamente os achados histopatológicos de 343 mulheres menopausadas com líquido intracavitário ao exame ultrassonográfico, não observaram nenhum caso de neoplasia de endométrio em pacientes com espessura de eco endometrial inferior à 3mm e concluíram que a investigação da cavidade uterina naquele grupo de pacientes deve ser realizada apenas quando a espessura do eco endometrial for superior a 3 mm ou o líquido for ecogênico.…”
Section: Discussionunclassified
“…Tal achado, entretanto, constitui um viés do estudo, visto que tais pacientes possuíam também espessamento endometrial. Topçu et al (2015) analisaram o endométrio de 141 pacientes na pós menopausa com presença de líquido intracavitáro na USTV e não foi encontrada nenhuma patologia pré maligna ou maligna. Takacs et al (2005) analisando retrospectivamente os achados histopatológicos de 343 mulheres menopausadas com líquido intracavitário ao exame ultrassonográfico, não observaram nenhum caso de neoplasia de endométrio em pacientes com espessura de eco endometrial inferior à 3mm e concluíram que a investigação da cavidade uterina naquele grupo de pacientes deve ser realizada apenas quando a espessura do eco endometrial for superior a 3 mm ou o líquido for ecogênico.…”
Section: Discussionunclassified
“… 8 However, some authors assert that EFC may be associated with malignancy even in the presence of endometria measuring less than 4mm. 3 - 5 Another study group recommended endocervical sampling in asymptomatic, postmenopausal patients with EFC, even when endometrial thickness is 3mm or less; endometrial sampling was also recommended for patients with echogenic EFC and any amount of endometrial thickening. 10 The most striking finding about the relationship between EFC and malignancy was reported by Breckenridge et al, who showed that uterine or cervical carcinoma occurred in 16 of 17 patients (94%) with EFC.…”
Section: Discussionmentioning
confidence: 99%
“… 1 It has been suggested that a single layer endometrial thickness of 4 mm should be the cutoff value beyond which above endometrial sampling should be performed, regardless of EFC presence, and that the surrounding endometrium and its thickness should be a more important consideration than presence of fluid alone. 2 , 3 However, several studies have shown that the presence of EFC may indicate endometrial and cervical pathology. 4 , 5 Indeed, some investigators have reported cases of endometrial carcinoma that presented ultrasonographically with a thin endometrium in the presence of EFC.…”
Section: Introductionmentioning
confidence: 99%